27 Peer-lead basic airway training for foundation doctors. (17th November 2016) - Gomm, Edward; Chang, A
Abstract : Background: Choking and respiratory arrest are life threatening emergencies. Foundation doctors (F1s) are typically the first responders yet have limited clinical experience and life support training. Anecdotally many feel underprepared, lack the confidence to respond appropriately, and can be confused by unfamiliar equipment. Personal observation of F1s at simulation training consistently demonstrated delayed recognition and management of respiratory arrest. Aims: Our primary aim was to implement a teaching session to give F1s the skills and confidence to recognise and manage a respiratory arrest as first responders. Secondary aims were to review simple airway techniques and equipment, safely suction the airway and manage a choking adult. We also set out to quantify the number of F1s that correctly identified and managed respiratory arrest. Methodology: A survey was circulated to gauge F1s confidence with airway management and identify learning objectives. We delivered a peer-lead teaching programme of one-to-one OSCE-style sessions on a low fidelity part-task trainer. Anaesthetic trainees were recruited to deliver and debrief the sessions. We assessed the candidates' ability to recognise respiratory arrest and gathered feedback to assess the impact of the training. Results: Only 30% of the students correctly identified respiratory arrest and initiated assisted breaths. Their self-rated confidence in airway management improved from a mean of 4/10 to 7.9/10. All F1s described the session as very useful to their job role and pitched at the right level. Discussion. We identified a training need for F1 doctors in managing basic airway emergencies and delivered a structured session to address their skills and confidence in these situations. These were well received by the trainees. Conclusions: We delivered a focused teaching session to address the needs of F1s doctors in managing airway problems in hospital. It was well received and we aim to expand its delivery to other sites regionally.